Social media usage and activism by non-western budding PR professionals during crisis communication - Kutoglu Kuruc, Ulfet; Opiyo, Baruck (Emerald Group Publishing Ltd, 2020)
Purpose A number of studies have documented the use and popularity of social networking sites among Millennials and late Millennials, especially in Western countries. However, the usage of these sites by non-Western young adults/late Millennials has just barely begun. Informed by literature and findings of recent research on audience information-seeking behavior and principles governing the usage of social media to obtain and disseminate crisis-related information, the purpose of this paper is to employ survey research to examine how senior PR-track non-Western late Millennial university students use social media to obtain and/or disseminate information on issues they perceived as crises. Design/methodology/approach A combination of survey research and critical communication methods were used to gather and analyze data from a sample of future non-Western budding PR professionals. Survey research was designed and used to investigate social media use among PR-major students studying at a large State University in the Mediterranean region to probe their perceptions of these media as forums for activism during moments of crisis. Questionnaire was designed to elicit responses on social media use and perceptions on a range of crisis-communication related issues, and their responses on the Likert scale that were later analyzed using the SPSS (version 21) program. Findings These future PR professionals appreciated the suitability of social media in disseminating crisis-communication messages. They also highlighted challenges that unethical use of such platforms pose to PR professionals. Social network sites were reported to be the most popular social media platforms used during crisis communication. Even though the respondents widely reported using social media to disseminate information during crisis situations - and answered in the affirmative that the use of social media at such times could positively contribute to social change, they did not consider themselves as activists who actively contribute to fostering of peace and justice. Originality/value A number of studies have documented the use of social networking sites among Millennials especially in Western countries. However, the usage of these sites by non-Western late Millennials has just barely begun. This paper attempts to do this. The study explored social media usage by the non-Western late Millennial PR-track university students. Attempts were also made to elicit such PR professionals' perceptions of whether social media contribute to activist movements and social change during crisis, and whether they physically acted as activist on social media to contribute to the improvement of societal ills, and to bring local/global peace or not.
Keywords: Ethics; Public relations; Activism; Social media usage in crisis communication